The effect of two-step surface treatment by hydrogen peroxide and silanization of flax/cotton fabrics on epoxy-based laminates thermomechanical properties and structure - Mateusz Barczewski (Journal of Materials Research and Technology, 2020)
The epoxy composites reinforced with flax/cotton fibers subjected to two surface treatments were prepared by hand lay-up method. Flax/cotton fabrics were subjected to bleaching using hydrogen peroxide, silanization, and two-step modification consisting of both methods. The effects of these treatments were assessed by Fourier Transform Infrared Spectroscopy (FTIR) and the fabric color was examined with accordance to CIELab method. The produced composites were subjected to the assessment of mechanical properties using static tensile and flexural tests. Moreover, impact resistance was evaluated by drop impact tests and the Charpy method. The effect of surface treatment of flax/cotton fabrics on epoxy-based composites thermomechanical properties were studied using dynamic thermomechanical analysis (DMTA) and related to structural changes investigated with scanning electron microscopy (SEM). The realized research showed that the use of a two-stage surface modification of fibers allows the production of composites with increased interfacial adhesion, as well as enhanced mechanical properties in comparison to materials manufactured using unmodified fabrics.